A companion to Terence - Augoustakis, Antony; Traill, Ariana, 1969-; Thorburn, John E. (Chichester, West Sussex [U.K.] ; Malden, Mass. : Wiley-Blackwell, 2013)
"A Companion to Terence offers the first comprehensive collection of essays on Terence in English. It includes a detailed study of Terence's plays, situating them in their socio-historical context and exploring their reception from the Classical through late antiquity, the Middle Ages, the Renaissance, to present day literature and performance. Each chapter discusses key issues in Terence, including Terence's relationship with his Greco-Roman models, his language and style, the question of performance and dramatic technique, and the socio-political background that shapes the themes, characters, structures, and cultural-political concerns. A Companion to Terence is a useful research tool for the growing number of scholars, students and critics of Terence and Roman comedy"--
Machine generated contents note: Notes on Contributors Acknowledgments Introduction Antony Augoustakis and Ariana Traill PART I TERENCE AND ANCIENT COMEDY 1. Terence and Greek New Comedy Peter Brown 2. Terence and the Traditions of Roman New Comedy George Fredric Franko 3. Terence and Non-Comic Intertexts Alison Sharrock 4. Fabula Stataria: Language and Humor in Terence Heather Vincent 5. Meter and Music Timothy J. Moore PART II CONTEXTS AND THEMES 6. Terence and the Scipionic Grex Daniel P. Hanchey 7. opera in bello, in otio, in negotio: Terence and Rome in the 160s BCE John H. Starks, Jr. 8. Religious Ritual and Family Dynamics in Terence T. H. M. Gellar-Goad 9. Gender and Sexuality in Terence Sharon L. James 10. Family and Household in the Comedies of Terence Z.M. Packman 11. Masters and Slaves Evangelos Karakasis PART III THE PLAYS 12. Andria Robert Germany 13. Heauton Timorumenos Eckard Lefevre 14. Eunuchus David M. Christenson 15. Phormio Stavros Frangoulidis 16. Hecyra Ortwin Knorr 17. Adelphoe Ariana Traill PART IV RECEPTION 18. History of the Text and Scholia Benjamin Victor 19. Terence in Latin literature from the Second Century BCE to the Second Century CE Roman Muller 20. Terence in Late Antiquity Andrew Cain 21. Hrotsvit of Gandersheim Christianizes Terence Antony Augoustakis 22. 'Thou shalt present me as an eunuch to him': Terence in Early Modern England Martine van Elk 23. mulier inopia et cognatorum neglegentia coacta: Thornton Wilder's Tragic Take on The Woman of Andros Mathias Hanses 24. Terence in Translation John Barsby 25. Performing Terence (and Hrotsvit) Now Mary-Kay Gamel General Index Index Locorum.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Terence -- Criticism and interpretation; Latin drama (Comedy) -- History and criticism; Theater -- History -- To 500.; Theater -- Rome; Electronic books